1996
DOI: 10.1109/61.489343
|View full text |Cite
|
Sign up to set email alerts
|

Event timing and shape analysis of vibration bursts from power circuit breakers

Abstract: Abstmct4oninvasive vibmtion diagnostic techniques plf? implemented to assess the mechanical condition of power cizcuit breakers. A diagnostic system, the Prototype Commercial PoltaMe Diagnostic System (E"DS) has been developed Hardware of the €"DS includes a poltable computer, and a data acquisition unit and computer communication cruds. Signal pmcessing techniques include the discrete energy sQCstics envelope, short-time p w e r spectnmq timing extraction algorithm and chi-square based shape test Decision-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(22 citation statements)
references
References 4 publications
0
22
0
Order By: Relevance
“…In the actual process of analysis, finding out the characteristic quantity by the analysis of collected vibration information, try to represent the process by the least characteristic parameters, so as to distinguish difference between normal and abnormal state. But a lot of time domain analysis of the characteristics of the vibration signal showed that the dispersion is bigger, poor repeatability and also found some vibration waves whose time domain are different obviously are normal waves, and the identical vibration could have bigger differences in local by sampling again and disposing [5]. Therefore, only by using time domain index as characteristics of vibration signals of circuit breaker operation is not scientific.…”
Section: The Vibration Monitoring Of Switchingmentioning
confidence: 99%
“…In the actual process of analysis, finding out the characteristic quantity by the analysis of collected vibration information, try to represent the process by the least characteristic parameters, so as to distinguish difference between normal and abnormal state. But a lot of time domain analysis of the characteristics of the vibration signal showed that the dispersion is bigger, poor repeatability and also found some vibration waves whose time domain are different obviously are normal waves, and the identical vibration could have bigger differences in local by sampling again and disposing [5]. Therefore, only by using time domain index as characteristics of vibration signals of circuit breaker operation is not scientific.…”
Section: The Vibration Monitoring Of Switchingmentioning
confidence: 99%
“…In order to get the CB operating characteristics, preventive test is adopted in the preventive maintenance. This kind of method has a series of disadvantages, including timeconsuming, frequent operation and excessive maintenance; all of this will reduce the reliability of the CB and bring negative influence [1,2]. So vibration diagnostic techniques of CB have gradually become a research hotspot in recent years [3].…”
Section: Introductionmentioning
confidence: 99%
“…Mechanical fault occupies a large proportion in the high voltage circuit breaker fault. Therefore, mechanical faults were extensively studied at present [1][2][3].…”
Section: Introductionmentioning
confidence: 99%